P 103 Aggressiveness of martial artists correlates with reduced temporal pole gray matter concentration. Issue 10 (October 2017) - Breitschuh, S.; Schöne, M.; Tozzi, L.; Kaufmann, J.; Strumpf, H.; Fenker, D.; Frodl, T.; Bogerts, B.; Schiltz, K.
Abstract : Theoretical background: Perception and practice of violence have, aside from reactive components, also hedonistic aspects that are associated with positive arousal (appetitive aggression). Earlier studies have predominantly investigated the etiology of aggressive behavior in forensic and psychiatric patients. The present study examined structural brain abnormalities in healthy people inclined to violence (martial artists) compared to healthy controls not showing violent behavior. Methods: Aggressiveness was assessed in 21 male healthy martial artists and 26 age-matched male healthy controls using the Freiburg personality inventory (FPI-R) and the aggressivity factors questionnaire (FAF). Participants then underwent structural T1-weighted MRI scanning. Differences in local gray matter (GM) were analyzed using voxel-based morphometry (VBM). A whole-brain analysis of the main effects of group and aggressivity (FAF) as well as their interaction was computed, using a threshold of p  < .001, followed by a cluster-level p FWE  < .05 to account for multiple comparisons. All analyses were controlled for age and total intracranial volume. Results: There was no significant main effect of group or aggressiveness in predicting GM concentration. Nevertheless, an interaction effect between group and aggressiveness was evident in a cluster comprising the left temporal pole and left inferior temporal gyrus ( F -test, whole-brain: p  < .001, cluster-level: p FWE  = .017;Fig. 1 ). Post-hoc analysis revealed a significant negative partial correlation between aggressiveness and mean GM concentration within the cluster in martial artists ( r  = −.71, p  = .001) and a significant positive one in healthy controls ( r  = .54, p  = .007) (Fig. 2 ). Discussion: Martial artists and controls displayed opposite correlations between aggressiveness and temporal GM: while they were positively correlated in controls, they correlated inversely in martial artists. Earlier studies reported decreased regional GM volumes in this region within diverse aggressive psychiatric populations, for example patients affected by psychopathy(Ermer et al., 2013) or impulsive-aggressive personality disorder (Dolan et al., 2002 ). The temporal pole and inferior temporal gyrus are relevant for emotional regulation and aggression control (Dolan et al., 2002 ) and display alterations in antisocial or violent behavior (Wong et al., 1997 ). The increased GM concentration of these areas in aggressive healthy controls might reflect a stronger top-down inhibition of their aggressivity. Martial artists, on the other hand, might be able to release their aggressivity in fights, thus showing reduced need for regulation and lower GM concentration in this region.